Upstream Beer Stabilisation during Wort Boiling by Addition of Gallotannins and/or PVPP - Withouck, H.; Boeykens, A.; Jaskula, B.; Goiris, K.; De Rouck, G.; Hugelier, C.; G. Aerts, G. Aerts (BrewingScience, 2010)
Addition of stabilisation products in the upstream brewing process is a very convenient way of physico-chemical stabilisation without the need for extra filtration or the risk of beer losses. Therefore, in this study the use of appropriate stabilisation products upstream the brewing process, more specifi cally at the end of wort boiling, have been evaluated in relation to improved colloidal stability. Applications of PVPP (Polyclar 10, ISP) and gallotannins (Beerotan Q, BFTI) have been investigated. The lowest gallotannin levels (wort boiling: 5 g/hL; contact time in boiling kettle: 3 minutes) are already sufficient to obtain enhanced stability due to adequate removal of haze- sensitive proteins. Furthermore, the addition of 10 g/hL PVPP has an explicit effect on the amounts of polyphenols, which results in an improved colloidal stability. Lowering pH at mashing-in also results in improved physico-chemical properties and flavour stability.